Regional contributions of D-serine to Alzheimer’s disease pathology in male AppNL–G–F/NL–G–F mice - Ni, Xiance; Inoue, Ran; Wu, Yi; Yoshida, Tomoyuki; Yaku, Keisuke; Nakagawa, Takashi; Saito, Takashi; Saido, Takaomi C.; Takao, Keizo; Mori, Hisashi (Frontiers in Aging Neuroscience, 2023)
Background: Neurodegenerative processes in Alzheimer’s disease (AD) are associated with excitotoxicity mediated by the N-methyl-D-aspartate receptor (NMDAR). D-Serine is an endogenous co-agonist necessary for NMDAR-mediated excitotoxicity. In the mammalian brain, it is produced by serine racemase (SRR) from L-serine, suggesting that dysregulation of L-serine, D-serine, or SRR may contribute to AD pathogenesis. Objective and methods: We examined the contributions of D-serine to AD pathology in the AppNL-G-F/NL-G-F gene knock-in (APPKI) mouse model of AD. We first examined brain SRR expression levels and neuropathology in APPKI mice and then assessed the effects of long-term D-serine supplementation in drinking water on neurodegeneration. To further confirm the involvement of endogenous D-serine in AD progression, we generated Srr gene-deleted APPKI (APPKI-SRRKO) mice. Finally, to examine the levels of brain amino acids, we conducted liquid chromatography–tandem mass spectrometry. Results: Expression of SRR was markedly reduced in the retrosplenial cortex (RSC) of APPKI mice at 12 months of age compared with age-matched wild-type mice. Neuronal density was decreased in the hippocampal CA1 region but not altered significantly in the RSC. D-Serine supplementation exacerbated neuronal loss in the hippocampal CA1 of APPKI mice, while APPKI-SRRKO mice exhibited reduced neuronal death and astrogliosis compared with APPKI mice. Furthermore, APPKI mice demonstrated marked abnormalities in brain amino acid levels that were partially reversed in APPKI-SRRKO mice. Conclusion: These findings suggest that D-serine promotes excitatory neuronal damage in AD brains and that reducing brain D-serine can partially attenuate neuronal loss and reactive astrogliosis. Therefore, regulating SRR could be an effective strategy to mitigate NMDAR-dependent neurodegeneration during AD progression.